Effect of Yea Sacc1026 Supplementation on Feed Intake and Rumen Fermentation in Buffalo Calves during Summer Season - Singh, Harjap (Indian Journal of Animal Nutrition, 2018)
The study was carried out with eight apparently healthy male buffalo calves to study the effect of Saccharomyces cerevisae (Yea Sacc1026)supplementation on rumen microbial abundance during summer season. The animals were divided into three groups of four each. Group I (Pre-summer), Group II ( Summer control) and Group III ( Summer treatment). Same animals were used in pre-summer and summer control groups. The animals of Group III were supplemented with Yea Sacc1026 @ 1 bolus (consisting of 25 billion live yeast cells) / animal per day. The results revealed that there was significant (P<0.05) decrease in total bacterial and total protozoal counts in group II and their levels were restored to normal after supplementation of Â Yea Sacc1026. Â During summer season there was significant increase in the percentage of holotrichs and significant decrease in percentage of entodiniomorphs. However following supplementation of Yea Sacc1026,there was no significant change in percentage of holotrichs and entodiniomorphs as compared to pre summer and summer control groups. It can be concluded from present investigation that supplementation with Yea Sacc1026 can be useful in order to improve the rumen microbial population in buffalo calves during summer season.